MORTALIDADE EM GESTANTES POR COVID-19 NO ESTADO DO MARANHÃO - OLIVEIRA, Paulo Henrique Queiroz de (2024)
Introduction: In Brazil, there was an increase in the number of maternal deaths in 2021 when compared to previous years. According to the Pan American Health Organization , the country had a Covid-19 fatality rate in pregnant women of 7.2% this year, despite the actions developed by the states and ministry of health, with the aim of improving care. pregnant women and the quality of data related to this context. However, there is an underlying concern that Covid-19 fatality and mortality rates may be underestimated due to underreporting of Covid-19 infections among the general public and pregnant women.Objective: To analyze mortality from Covid-19 among pregnant women, from 2020 to 2022, in the state of Maranhão. Methods: This is a longitudinal and cross-sectional descriptive study in which mortality among pregnant women due to Covid-19 (SARS-CoV-2) was analyzed from 2020 to 2022, using the probabilistic record linkage method. Secondary data from the information systems e-SUS Notifica, SIVEP-Gripe, SIM and SI-PNI were used. Results: The SIM contained 7,670 deaths from all basic causes in women aged 10 to 49 years, in the period between 2020 and 2022. Of the total deaths, 322 were classified as maternal deaths and specifically 71 were reported with an underlying cause B34.2, confirmed for Covid-19. In the total period, the percentage of maternal deaths due to Covid-19 in relation to total maternal deaths was 22%. The largest proportion of women who died were aged between 25 and 29 years (25.4%), were mixed race (60.6%), single (45.1%) and had eight to eleven years of education (47. 1%). Furthermore, it was observed that housewives, rural and commercial workers were the most frequent occupations and only 4.2% of pregnant women who died had a vaccination record in the SI-PNI. Deaths were more frequent in the cities of Imperatriz (14.1%), São Luís (12.7%), Balsas (7%) and São José de Ribamar (5.6%). It was also possible to identify an underinformation rate of 12.67% and an underreporting rate of 8.45%. Adding the cases of deaths in pregnant women due to Covid-19 reported in SIM (71) plus the cases of underreporting and underinformation found in the Linkage analysis (15), we have a total of 86 deaths due to Covid-19 in pregnant women, which corresponds at a rate of 21.12% more compared to official notifications. Final Considerations: Underreporting and underreporting of deaths in pregnant women due to Covid-19 is a significant and multifaceted problem, which can have important implications for public health and the management of health crises. To effectively prevent and control outbreaks, epidemics and pandemics, it is essential to have detailed, updated and qualified information on the profile of the pathologies involved. Furthermore, implementing robust and well-structured health information systems can facilitate data integration and sharing, promoting a more efficient and coordinated response to public health crises.